RETRACTED: From molecular mechanism to plant intervention: the bidirectional regulation of inflammation and oxidative stress in bone aging - Li, Qi; Zhao, Xiumei; Wang, Anning; Hang, Tingting; Zhao, Jianpeng; Zhang, Shengkai; Zeng, Lingfeng; Wang, Weiguo (Frontiers in Endocrinology, 2025)
This article systematically elaborates the central role of inflammatory response and oxidative stress in osteoporosis (OP) and cartilage injury, and reveals the molecular mechanism by which the two damage bone homeostasis through NF-κB, RANKL and other signaling pathways. Studies have shown that plant natural products (such as hesperidin, curcumin, Epimedin B, etc.) can improve bone metabolism imbalance and delay the process of bone aging by regulating inflammatory factors (TNF-α, IL-1β) and antioxidant pathways (Nrf2/HO-1). Osteoporosis and cartilage damage promote each other to form a vicious cycle, and the intervention of plant active ingredients can target this common pathological process. Based on the current evidence, the strategy of combining anti-inflammation, anti-oxidation and mechanical regulation may provide a new direction for the prevention and treatment of bone aging-related diseases.